USING TOPOGRAPHIC ELEVATIONS IN CREATING TRAFFIC SCENARIOS IN JUNCTIONS - Bogdan Stefan Florescu; Laurentiu Racila; Alexandru Oprica; Lucian Matei; Ilie Dumitru (Journal of Industrial Design and Engineering Graphics, 2019)
Due to the changes in the road traffic caused by the continuous growth of the motor fleet, the increase of the existing fleet mobility index and the increase in the number of vehicles passing through the city, it is usually necessary to intervene in the road traffic with traffic lights. It is necessary to transform the old system of the traffic network into a new efficient system, corresponding to a new road infrastructure with increased vitality. The paper aims to demonstrate the use the elevation from topographic equipment’s to design the junctions vertical and horizontal signalization, in every detail.